CONTEXT-AWARE SMART MIRROR FOR HOME ENVIRONMENTS (CASM-HOME SYSTEM) - Dr. Namratha S.; Mr. Shaik Mohammed Zakir; Ms. Anjum Begum; Ms. Sapura; Ms. Komal (International Educational Journal of Science and Engineering, 2026)
This paper presents the design and implementation of a context-aware smart mirror system for home environments using a Raspberry Pi platform. The system integrates a two-way mirror with a digital display to provide real-time information such as time, weather updates, news and calendar events while maintaining the functionality of a conventional mirror. The proposed system uses the MagicMirror² framework to enable modular and customizable display features. The primary objective is to develop a low-cost and practical smart interface that enhances daily convenience without requiring additional devices. The system operates continuously with minimal user interaction and demonstrates stable performance in real-time data display. The proposed solution highlights the potential of combining embedded systems with user-centric design to create efficient smart home interfaces.